A need for anthropometric studies on handicapped people - Batogowska, Anna (Anthropological Review, 1984)
A need for standarization of diameters of human body for industrial purposes is well recognized today and appropriate data utilized by engineers designing various sorts of machinery and equipment. Physically invalid people have a special need for everyday use of specific equipment while dimensions of their bodies and dynamics of movements are different from usual standards. Thus appears a need for anthropometric studies of handicapped people forming a basis for a project undertaken by the Group of Ergonomic Problems of Rehabilitation. Details of the proposed study are described in the present paper.